Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita SPLDV Berdasarkan Tahapan Newman - Rahajeng Rahastiana Fimillatika; Haerudin Haerudin (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2023)
This study aims to observe the errors of class IX junior high school students in solving the problem of a two-variable system of linear equations in the form of a narrative math problem. The research subjects were 24 students of class IX. This research instrument uses 3 narrative mathematical problems of a two-variable linear equation system according to the Newman error analysis indicator. A qualitative descriptive approach was used in this study. The results obtained, some students have difficulty on indicators to solve problems involving a system of linear equations of two variables. Based on Newman's error analysis, the causes of student errors in solving two-variable linear equation system narrative math problems are: (1) 35% for reading errors in the very low category are caused by difficulties in interpreting the meaning of words or terms in the problem; (2) 61% for comprehension errors in the low category due to students not writing down the known and asked elements; (3) 50% for transformation errors in the very low category is due to difficulties in determining procedures and formulas; (4) 59% for process skill errors in the low category caused by errors in the calculation process; and (5) 58% for encoding errors in the low category were caused by students not writing conclusions.